(untitled) (Research, Society and Development, 2021)
This article presents the importance of implementing a cistern reservoir to capture rainwater in the rural school, being used as a viable option to minimize the problem related to water scarcity. The school is located in the region of the hydrographic basin of the Jauru river in the Pantanal of Mato Grosso, the degraded areas with loss of capacity of the springs, added to the geological and geomorphological aspects of the region have caused water scarcity even in the largest wetland of the planet. The objective of this work was to characterize the importance of installing a cistern for rainwater catchment at the State School 12 de Outubro in the hydrographic region of the Jauru River-MT. The system presented is a project developed in the Brazil/Bolivia border region and is an alternative for rainwater harvesting. The cistern was implemented in a rural school in the city of Cáceres-MT through the Project for the construction of dams and cisterns involving the settlements, public authorities and researchers. For the development of the work, a literature review was carried out and an online semi-structured questionnaire was applied to education professionals about the perception of the use of water collected from rain and the importance of building a cistern at school. The work proposes, given the problem of water scarcity at school, the importance of capturing rainwater, considering that the region suffers from a lack of water, especially during the dry season.